Utbildning, målmedvetenhet och vithet: Görande av klass bland kvinnor och män med polska föräldrar - Runfors, Ann (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2023)
Based on an analysis of interviews with women and men who grew up in Sweden with one or two Polish parents this article argues that ethnologists can and should contribute to the research on class by using constructivist theory and illuminating processes in which class is done. Leaning on Beverly Skeggs poststructuralist writing on class it analyses how the interviewees make class with help of the capital they possessed and in relation to class as a system of classification and of judgement. Most positioned themselves as middleclass by using socially upgrading criteria’s in the system of classification, such as higher education and dedication. While most lacked economic capital, these was the types of capital many of them had within reach and used. The whiteness the interviewees where ascribed in turn proved to upgraded them socially. It furthermore functioned as a cultural capital as it ensured their passing as majority members and thereby the use value of education as well as the ability to convert other forms of capital. It made their making of middleclass positions possible.